PEER FEEDBACK ON STUDENTS’ ABILITY TO WRITE ENGLISH ESSAYS - Moh. Hanafi (STKIP PGRI Trenggalek, 2020)
This research was aimed to investigate the effectiveness of peer feedback on students’ writing ability write English essays. A pre-experimental research was used as the research design and the students of the second semester of English Department who took the Academic Reading and Writing course was chosen as the sample of this study. A pretest was administered before the students started experiencing peer feedback as the research treatment while a posttest was conducted after the students got all the treatment of peer feedback. However, during the pandemic of Covid 19, all the research activities including pretest, treatment and posttest were done online. The pretest result showed that the students’ writing ability was quite low. The maximum score was 75, the minimum score was 35 while the mean score of the class was 54.83. After the students got a series of treatment of the peer feedback, the posttest result showed improvement. The maximum score was 88, the minimum score was 55 while the mean score was 72.38. It means that the posttest result was 17.55 points higher than the pretest result. Statistical analysis was also done to test the hypothesis testing. Based on the tests of assumption of homogeneity and normality testing, it showed that the data was homogeneous as well as normal so the parametric statistical analysis was used to analyze the data. The paired sample t-test was used in this test and it showed that the significant value obtained was lower than the level of significance of 0.05 (0.000<0.05). Therefore, it can be concluded that the null hypothesis was rejected. In the other words, it can be concluded that the students got better ability in writing English essays after experiencing the peer feedback. It means that the peer feedback has a significant effect on students’ ability to write English essays.